Geriatric Family Support and Diabetic Type-2 Glycemic Control - Shiva Heidari; Maryam Nouri Tajer; Fateme Hosseini; Mehrnoush Inanlou; Fateme Golgiri; Fateme Shirazi (University of Social Welfare & Rehabilitation Sciences, 2008)
Objectives: As the most part of geriatric (65 years and older) diabetic care is given at home, family support has an important role in their blood sugar level control care. This study aimed to assess the relationship between family support and blood sugar level control in such elderly suffering type-2 diabetes. Methods & Materials: Via descriptive-correlative study, one hundred fifty geriatric patients with type-2 diabetes, who referred to Institute of Endocrinology and Metabolism in Iran University of Medical Sciences were selected. Samplings based on nonrandomized and convenience. The questionnaire consisted of three sections: demographic data glucose-labeled hemoglobin (HbA1C) and received-perceived family support by applying the standard questionnaire of "Diabetes Social Support-Family Version" format. Data were analyzed by SPSS version 15 by using Chi-square and Pierson Tests. Results: Results showed a significant relationship between family support and glycemic control (r=-0.56, P<0.0001). Also there were significant relationships between family support, gender and marital status (P<0.0001). There were also significant relationships between glycemic control and marital status (P=0.02), financial status (P=0.04) and educational level (P=0.05). Conclusion: Findings of this research added further evidence about the impact of family support on the health of older adults with diabetes. These findings suggest using family centered nursing interventions and collaboration of family members in care of the elderly with type-2 diabetes.